Analisis Faktor-Faktor Yang Mempengaruhi Semangat Kerja Karyawan Pada PT. Arkananta Apta Pratista Kabupaten Penajam Paser Utara - Sunaryo, Octaningrum; Palinggi, Yonathan; Akbar, Ali (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2019)
Abstract:The purpose of this study is to know 1). the influence of discipline, cooperation and responsibility on employee morale at PT. Arkananta Apta Pratista in Penajam Paser Utara. 2). The dominant variable influences the employee morale at PT. Arkananta Apta Pratista in Penajam Paser Utara.The reality of the problems that researchers see and observe through research activities on employees of PT. Arkananta Apta Pratista in Penajam Paser Utara is the level of employee morale is still not optimal. Especially that can be seen from the factors that are caused by discipline, cooperation and responsibility. So that problems arise at PT. Arkananta Apta Pratista at this time, where the employees began to idle in their work, it was also seen that the employees who worked during the hours of the internet played on their cellphones even though there were still unfinished jobs at their desks.The population in this study was taken from employees of PT. Arkananta Apta Pratista as many as 163 employees and the study sample was 49 people using the purposive sampling method. The analytical tool used is multiple linear regression analysis using the test hypothesis F and t.The results of the calculation of the F test (simultaneous / joint correlation), obtained F count is 49.725, while the value of the F table obtained a value of 2.81 this means that (F count 49.725> Ftable 2.81), so that it can be said to be disciplinary variables, Collaboration and responsibility together (simultaneous) are able to show its influence on the morale of the employees of PT. Arkananta Apta Pratista. Then the first hypothesis is accepted because it is proven to be true.The number R is 0.876 this is that the correlation or relationship between discipline, cooperation and responsibility with employee morale is very strong relationship. The three independent variables were able to explain changes in morale by 75.3% while the remaining 24.7% was influenced by other variables not included in this study such as leadership, career development and so on.From the three results of the partial correlation test above the value of the responsibility variable is the highest compared to the other variables, so that the variable responsibility is the most dominant variable influencing the morale of the employees of PT. Arkananta Apta Pratista in Penajam Paser Utara then followed by variables of cooperation and discipline. From the description, it can be concluded that the second hypothesis in this study was rejected because it was not proven true.Keywords: Discipline, Cooperation, Responsibility, Work Spirit